2017
DOI: 10.1177/1010428317705337
|View full text |Cite
|
Sign up to set email alerts
|

S100A11 regulates renal carcinoma cell proliferation, invasion, and migration via the EGFR/Akt signaling pathway and E-cadherin

Abstract: S100A11 is a S100 protein family member that contributes to cancer progression. Upregulated in human renal cancer tissues, S100A11 may be a prognostic marker for clear cell renal cell carcinoma, but how it functions in cancer is uncertain. Thus, we studied S100A11 and noted knockdown of S100A11 using short hairpin RNA, which inhibited proliferation, invasion, and migration of renal carcinoma cells as well as increased expression of E-cadherin and decreased expression of epidermal growth factor receptor/Akt in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Consistent with cell proliferation assay, stably down‐regulating S100A11 using shRNA inhibited colony formation in RBE and HCCC 9810 cells (Figure E‐G, K‐M) and colony formation increased obviously in RBE and HCCC 9810 cells after transfected with the S100A11 overexpression vector (Figure H‐J, N‐P). Cell cycle assay showed RBE cells and HCCC9810 cells were both arrested at G1 phase after knockdown of S100A11, which was consistent with other literature findings (Supplementary Figure S3A‐D). This result just happened to explain why proliferation was inhibited after silencing S100A11 in RBE and HCCC9810 cells.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with cell proliferation assay, stably down‐regulating S100A11 using shRNA inhibited colony formation in RBE and HCCC 9810 cells (Figure E‐G, K‐M) and colony formation increased obviously in RBE and HCCC 9810 cells after transfected with the S100A11 overexpression vector (Figure H‐J, N‐P). Cell cycle assay showed RBE cells and HCCC9810 cells were both arrested at G1 phase after knockdown of S100A11, which was consistent with other literature findings (Supplementary Figure S3A‐D). This result just happened to explain why proliferation was inhibited after silencing S100A11 in RBE and HCCC9810 cells.…”
Section: Resultssupporting
confidence: 91%
“…Our results were in accordance with previous reports, which demonstrated that S100A11 promoted cell proliferation of breast cancer and pancreatic carcinoma . Additionally, cell cycle assay revealed cells were arrested in G1 phase in both RBE and HCC9810 cells after silencing S100A11, which was consistent with the research in renal carcinoma cells . Collectively, we can draw a conclusion that cells in G1 phase are unable transit to S phase after silencing S100A11.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[13][14][15] In contrast, as the bioinformatic results suggest, 4T1 cells cultured in a sparse environment were more likely to be connected to metabolism events, especially for lipids or cholesterol, which may associated with cancer-cell growth or survival. [29][30][31][32] Hypoxia, which usually happens in tumour sites where cancer cells have a high speed of proliferation marked with Ki67 upregulated, can induce the expression of S100A11 to regulate the motility of smooth muscle cell. JAM-1 was decreased in samples from dense cultures, which was verified by a western blot.…”
Section: Figurementioning
confidence: 99%
“…The binding of EGF to an EGF receptor (EGFR) can promote cell survival and proliferation (Cohen et al ., ; Prenzel et al ., ). In addition, EGFR signaling also favors cell differentiation, migration, and invasion in vitro (Abd El‐Rehim et al ., ; Liu et al ., ; da Rosa et al ., ). In contrast to TGF‐β signaling, EGF/EGFR signaling predominantly functions as a promoter in tumorigenesis (Arteaga and Engelman, ).…”
Section: Introductionmentioning
confidence: 99%